Rate of convergence of a group of deviations on sets of $\bar{ψ}$−integrals - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We study functionals that characterize the strong summation of Fourier series on sets of $\bar{ψ}$−integrals in the uniform and integral metrics. As a result, we obtain estimates exact in order for the best approximations of functions from these sets by trigonometric polynomials.